NASA's elementary and secondary education program review and critique - Quinn, Helen R.; Schweingruber, Heidi A.; Feder, Michael A. (National Academies Press, 2008)
"This report focuses on NASA's K-12 education activities, as mandated by congressional language in the 2005 reauthorizing legislation for the agency"--from Introduction (p. 11).